2006
DOI: 10.1038/sj.npp.1301257
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of the Ampakine Farampator on Memory and Information Processing in Healthy Elderly Volunteers

Abstract: Ampakines act as positive allosteric modulators of AMPA-type glutamate receptors and facilitate hippocampal long-term potentiation (LTP), a mechanism associated with memory storage and consolidation. The present study investigated the acute effects of farampator, 1-(benzofurazan-5-ylcarbonyl) piperidine, on memory and information processes in healthy elderly volunteers. A double-blind, placebocontrolled, randomized, cross-over study was performed in 16 healthy, elderly volunteers (eight male, eight female; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…Further, modulation of AMPA receptors has been evaluated in schizophrenia. Ampakines are compounds that interact with AMPA receptors to modulate synaptic activity by allosterically binding to the receptors to facilitate synaptic transmission (Wezenberg et al, 2007). Meta-analyses of studies using multiple adjunct therapies found that ampakines were ineffective in reducing the positive symptoms of schizophrenia (Goff et al, 2008;Tuominen et al, 2005;Tuominen et al, 2006).…”
Section: Grip/abp-glua2 Binding Destabilized Accumulation Ofmentioning
confidence: 99%
“…Further, modulation of AMPA receptors has been evaluated in schizophrenia. Ampakines are compounds that interact with AMPA receptors to modulate synaptic activity by allosterically binding to the receptors to facilitate synaptic transmission (Wezenberg et al, 2007). Meta-analyses of studies using multiple adjunct therapies found that ampakines were ineffective in reducing the positive symptoms of schizophrenia (Goff et al, 2008;Tuominen et al, 2005;Tuominen et al, 2006).…”
Section: Grip/abp-glua2 Binding Destabilized Accumulation Ofmentioning
confidence: 99%
“…The compound failed to have an effect in a phase II study simulating shift work (Wesensten et al, 2007). Another AMPA potentiator of the same class, farampator, showed acute effects on short term memory in a preliminary study in aged healthy human volunteers (Wezenberg et al, 2007).…”
Section: E ␣-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid and mentioning
confidence: 99%
“…In addition, previous studies showed that regular ampakine administration would increase the expression of BDNF. Considering that ampakines can also cross the blood-brain barrier, are bioactive orally and improve cognitive function without obvious side effects, they are of great potential and in fact have been partially proved to be candidate for a range of neurological disability and disturbances, including Alzheimer's disease and Huntington's disease [58,[61][62][63] . We hypothesize that ampakines are beneficial to the neurocognitive problems found in OSA by its action in elevating endogenous BDNF level in the brain.…”
Section: Future Directionsmentioning
confidence: 99%